KERAGAMAN MAKANAN DAN HUBUNGANNYA DENGAN STATUS GIZI BALITA: ANALISIS SURVEI KONSUMSI MAKANAN INDIVIDU (SKMI) - Utami, Nur Handayani; Mubasyiroh, Rofingatul (PERSATUAN AHLI GIZI INDONESIA, 2020)
Food consumption is one of the vital things that can determine the nutritional status of children. One indicator of the dietary quality of children is dietary diversity. This analysis was carried out to analyze dietary diversity and its relationship to the nutritional status of under-five children in Indonesia. The analysis was carried out on the data of the Individual Food Consumption Survey (IFCS). A total of 5,395 children were sampled in this analysis. Food consumption was collected through 24hr recall. The dependent variable in this analysis is the nutritional status of children (weight for age). The main independent variable is dietary diversity. The results of the analysis show that the types of food consumed most by children under five in Indonesia are cereals, roots, and tubers while the types of food groups that are the least consumed are fruits and nuts. The results of the analysis also show that the higher the age, mother's education and the economic level, the more diverse the consumption of food. The diversity of consumption is also higher for children in urban areas. The results of the analysis show that the diversity of food consumed by infants is related to nutritional status. Less diverse consumption mainly increases the risk of children experiencing severe underweight, even though this relationship is weak. Conversely, less diverse consumption reduces the risk of overweight.